The Alumni Chronicles Issue No.3: September 2023 - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
This e-magazine is mainly focusing on Management of Business Records and how it is related to the management of alumni records as its core business. The Alumni can help with global admissions and recruitment efforts, career and professional development, local and state advocacy or lobbying and through their generous philanthropic support. All articles and write-ups included in this e-publication are based on research or non academic research of the university. The purpose of publishing this e-magazine is to record and bring us together through strengthening the engagement of the alumni in university and how to strengthen this relationship so that we can create meaningful values in return to our graduates through projects and programme of the university to reach its achievements which is related to the development of UiTM Sarawak alumni starting from the year 1973 until now. They are part of the history. One of the best parts is the network that comes with it. An alumni network connects you, as a graduate, with a number of professional contacts and other graduates from the university. "Being willing to share the lessons learned on your journey, strategies for meeting challenges, and find opportunities for growth and connection are a few good moves. It all starts with a question, ‘Hello, how can I help you?’”Last but not the least, strike for the best and strive for excellence throughout our most productive year at UiTM Sarawak.